2019
DOI: 10.1039/c9fo00758j
|View full text |Cite
|
Sign up to set email alerts
|

The impact of reduced red and processed meat consumption on cardiovascular risk factors; an intervention trial in healthy volunteers

Abstract: Reductions in red meat intake lowered LDL in men, but may have unfavourable short term impact on blood cell numbers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…[ [123][124][125][126][127][128][129][130][131][132][133][134][135] Dietary quality index An index combining the above criteria would allow the objective assessment of diet quality. Such indices would facilitate the implementation of dietary guidelines.…”
Section: Rationale Relevance and Comments Referencesmentioning
confidence: 99%
“…[ [123][124][125][126][127][128][129][130][131][132][133][134][135] Dietary quality index An index combining the above criteria would allow the objective assessment of diet quality. Such indices would facilitate the implementation of dietary guidelines.…”
Section: Rationale Relevance and Comments Referencesmentioning
confidence: 99%
“…The decline was up to 10% when vegans were compared with regular meat eaters and the affected cells included neutrophils, lymphocytes, monocytes, and eosinophils. In healthy individuals, reducing red and processed meat consumption for 6 weeks seems long enough to reduce HGB levels by 5%, platelet count by 10%, and WBC count by 27% 25 …”
Section: Diet and Drugsmentioning
confidence: 99%
“…Among the various foods, meat plays a key role in human diets, since it is the richest source of proteins, essential amino acids, minerals, vitamins, and other micronutrients (Lafarga and Hayes, 2014). However, several studies have reported that diets high in red and processed meats are associated with metabolic syndrome and cardiovascular disease (Simpson et al, 2019).…”
Section: The Frequency Of Consumption Of Selected Products Of Study Participantsmentioning
confidence: 99%